2000
DOI: 10.1038/sj.bjp.0703262
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into pharmacological antagonism of general anaesthesia

Abstract: 1 The eects of convulsant drugs, and of thyrotropin releasing hormone (TRH), were examined on the general anaesthetic actions of ketamine, ethanol, pentobarbitone and propofol in mice. The aim was to investigate the possibility of selective antagonism, which, if seen, would provide information about the mechanism of the anaesthesia. 2 The general anaesthetic eects of ketamine were unaected by bicuculline; antagonism was seen with 4-aminopyridine and signi®cant potentiation with 300 mg kg 71 NMDLA (N-methyl-DLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…This is an ED 50 dose for loss‐of‐righting reflex (Lingamaneni et al ., 2001), which is an animal model for unconsciousness. Behavioral observations and measurements of righting reflex were carried out as previously described (Little et al ., 2000; Lingamaneni et al ., 2001). Body temperature was maintained at 38 °C using a heating pad placed beneath the mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an ED 50 dose for loss‐of‐righting reflex (Lingamaneni et al ., 2001), which is an animal model for unconsciousness. Behavioral observations and measurements of righting reflex were carried out as previously described (Little et al ., 2000; Lingamaneni et al ., 2001). Body temperature was maintained at 38 °C using a heating pad placed beneath the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Propofol achieves these actions in part via allosteric regulation of GABA A receptors (Hales & Lambert, 1991; Krasowski et al ., 2001), and recent studies on knock‐in mutant mice suggest that these effects of propofol at the molecular level are of considerable behavioral significance (Jurd et al ., 2003). However, a variety of behavioral studies have shown that the anticonvulsant and sedative actions of propofol are incompletely blocked by GABA A receptor antagonists (Little et al ., 2000; Ohmori et al ., 2004), indicating that additional unidentified mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%
“…24 Finally, administration of the GABA A agonist muscimol to an intact animal does not result in general anaesthesia, nor can anaesthesia be reversed simply by administering a GABA A antagonist, such as bicuculline. 55 These caveats should not be taken as evidence that anaesthetic interactions with the GABA A receptor are unimportant in causing anaesthesia. For many anaesthetics, the potentiating effect of anaesthetics on the GABA receptors is a major component of their mode of action.…”
Section: Do Anaesthetics Preferentially Affect Presynaptic or Postsynmentioning
confidence: 99%
“…4 We know that GABA A receptors are not the only target for general anesthetics. 5 The NMDA receptor may also mediate the action of barbiturates. It has been reported that barbiturates decrease NMDAgated currents in the spinal cord but have no effect on amino acid pathway gated currents.…”
mentioning
confidence: 99%